Using water efficiently : technological options - Xie, Mie (World Bank WashingtonUS, 1993)
Examines briefly, sectoral water allocation in various countries and regions. Discusses and clarifies some of the definitions of water use efficiencies under various contexts. Presents estimates of sectoral efficiencies in irrigation and domestic/industrial water use, and provides intensive country examples. Reviews the technological and managerial options to improve water use effiency. Presents cost comparisons and management implications of alternatives.